KNOWLEDGE SHARING BEHAVIOUR: THE ROLE OF SELF-EFFICACY, ORGANISATIONAL JUSTICE AND ORGANISATIONAL TENURE - Olowodunoye, Stella A. (European Scientific Journal, ESJ, 2015)
There is dearth of information on the combining role of self-efficacy, organisation justice and organisational tenure in the literature and the unflinching role of these three variables in predicting knowledge sharing behaviour could not be overlooked. Therefore, this study investigated the role of self-efficacy, organisational justice and organisational tenure in knowledge sharing behaviour. Three hundred participants comprising of 148 males and 152 females between the age range of 23-47 years with the mean age of 32.62 and SD = 6.63 participated in the study. Self-efficacy Scale and Organisational Justice Scale were employed to gather data from the participants. The result of the Regression Analysis indicated that selfefficacy; organisational justice and organisational tenure significantly independently and jointly predicted knowledge sharing behaviour. The implications of these findings are that self-efficacy; organisational justice and organisational tenure played important roles in knowledge sharing behaviour among employees. The results of these findings were discussed in line with existing theories and literatures and recommendations were made